(untitled) (Heritage, 2023)
The paper interpreted the formation of the phenomenon of rebellion in Krleza’s novella The Great Master of All Scoundrels. The focus of the interpretation was the inner transformation of the main character, Ljubo Kraljevic. The trajectory of his consciousness was analyzed, from the refusal of responsibility for social events to the ambivalent state that unites the revolutionary ethos and the state of impotence. In this transformation of the main protagonist’s consciousness, an important role plays the typical expressionistic visionary state of the subject. A special aspect of the interpretation represents the examination of the ethical implications of the main character’s rebellious standpoint. Ljubo Kraljevic places himself in the center of the decentralized modern world and, after paranoid states, at the end of the novella he comes to the idea of "divine violence", at the same time not leaving the position of a victim of the social order. In the novella, Krleza actually shapes a subject who, although reaches a specific revolutionary ethic, is left without ways and practices to overcome his subordinate position in the social hierarchy.